Kompetensi Profesionalisme Guru Dalam Meningkatkan Mutu Pendidikan - Pawan, Fredy; Gasong, Dina; Tanduk, Rita (CV. ITTC INDONESIA, 2024)
The aim of this research is to determine whether there are differences in the teaching results of teachers who are committed to their duties and responsibilities based on educational professionalism competencies, in relation to the achievement of the students being taught. The research was conducted using a qualitative approach. Data collection procedures were carried out using observation, interviews, documentation studies and questionnaire methods. The data analysis method used in this research is qualitative and quantitative data analysis. The results of this research show that a number of teachers ± 63% of the teaching staff can be categorized according to educational competence and professionally carry out their duties. There is still a perceived shortage of teachers, so the allocation of additional teachers should be those who have competence and have a teaching certificate and a teaching certificate. Opportunities and challenges in improving the quality of education still require awareness from the government and all related parties, including teachers, to instill awareness of their professionalism and competence as educators whose success greatly influences the quality of the school outcomes they provide.